[Ekslibris] M. Radojewskiego / [Zbigniew Dolatowski]. - Dolatowski, Zbigniew (1927-2001) (1965)
Monogram mr, w środku napis: M. Radojewskiego. Sygn. aut. w obrębie kompoz., pod wyobrażeniem autograf aut. i data.